Recognition of 'self' and 'non-self' glycans by carbohydrate-binding proteins: structural and functional aspects - Vasta, Gerado (Henry Stewart Talks, 2012)
Functional aspects of the glycocalyx in innate immunity and development, Lectins as recognition and effector factors in innate immunity, F-type lectins: a novel lectin family, Structural basis of glycan recognition by F-lectins, Structural/functional aspects of galectins in development, immune regulation and as pattern recognition receptors, Subversion of the roles of host galectins by eukaryotic parasites